Investigating the morphology of the supernova remnant G349.7+00.2 in the medium with a density gradient - Yan, Jing-Wen; Lu, Chun-Yan; Wen, Lu; Yu, Huan; Fang, Jun (Research in astronomy and astrophysics, 2020)
G349.7 + 00.2 is a young Galactic supernova remnant (SNR) with a mushroom morphology in radio and X-rays, and it has been detected across the entire electromagnetic spectrum from radio to high energy γ-rays. Moreover, the remnant is interacting with a molecular cloud based on the observations in the radio and infrared band. The reason for the formation of the periphery and the dynamical evolution of the remnant is investigated using 3D hydrodynamical (HD) simulations. Under the assumption that the supernova ejecta is evolved in the medium with a density gradient, the shell is composed of two hemispheres with different radii, and the smaller hemisphere is in relatively dense media. The resulting periphery of remnant is consistent with detected ones, and it can be concluded that the peculiar periphery of G349.7+00.2 can be reproduced as the remnants interacting with the medium with a density gradient.